The role of major immune cells in myocardial infarction - Feng, Qiang; Li, Qirong; Zhou, Hengzong; Sun, Liqun; Lin, Chao; Jin, Ye; Wang, Dongxu; Guo, Gongliang (Frontiers in Immunology, 2023)
Myocardial infarction (MI) is a cardiovascular disease (CVD) with high morbidity and mortality worldwide, often leading to adverse cardiac remodeling and heart failure, which is a serious threat to human life and health. The immune system makes an important contribution to the maintenance of normal cardiac function. In the disease process of MI, necrotic cardiomyocytes release signals that activate nonspecific immunity and trigger the action of specific immunity. Complex immune cells play an important role in all stages of MI progression by removing necrotic cardiomyocytes and tissue and promoting the healing of damaged tissue cells. With the development of biomaterials, cardiac patches have become an emerging method of repairing MI, and the development of engineered cardiac patches through the construction of multiple animal models of MI can help treat MI. This review introduces immune cells involved in the development of MI, summarizes the commonly used animal models of MI and the newly developed cardiac patch, so as to provide scientific reference for the accurate diagnosis and effective treatment of MI.